The Predictive Ability of Psychological Resilience and Self-Efficacy in Professional Adjustment among Educational Counselors in Palestine: A Proposed Counseling Program (The International Journal for Scientific Research, 2026)
Study Objective: This study aimed to examine the predictive power of psychological resilience and self-efficacy in explaining professional adjustment among educational counselors in Palestine, as well as to propose a counseling program.Methodology: A descriptive correlational approach was employed, and data were collected using three instruments: the Psychological Resilience Scale, the Self-Efficacy Scale, and the Professional Adjustment Scale. The study sample consisted of 294 male and female counselors in Palestine, selected through cluster random sampling. Results: The findings revealed that the overall level of psychological resilience among educational counselors was high (M = 4.05). Statistically significant differences were found in psychological resilience based on gender, favoring males across all dimensions, as well as based on educational qualification. Specifically, doctoral degree holders scored higher in the domains of endurance and coping with stress, while both master’s and doctoral degree holders showed higher levels in self-confidence and optimism. The results also indicated that the overall level of self-efficacy was high (M = 4.00), with statistically significant gender differences favoring males, as well as differences based on educational qualification in the domain of efficacy, in favor of doctoral degree holders. Similarly, the level of professional adjustment was found to be high (M = 4.09), with statistically significant differences attributed to gender, again in favor of males. Furthermore, significant positive correlations were found between psychological resilience and self-efficacy (r = 0.786), psychological resilience and professional adjustment (r = 0.731), and self-efficacy and professional adjustment (r = 0.776), all at (α ≤ 0.01). Regression analysis showed that both psychological resilience and self-efficacy had a statistically significant predictive effect on professional adjustment (α ≤ 0.05), jointly explaining 64.1% of the variance. Recommendations: Strengthening self-efficacy development programs for educational counselors, as it is the variable that contributes most significantly to professional adjustment. This can be achieved through training courses that focus on building a sense of efficacy, decision-making skills, and the management of complex counseling situations.
Keywords: Psychological Resilience; Self-Efficacy; Professional Adjustment; Counseling Program